Effects of Turmeric Concentrate on Cardiovascular Risk Factors and Exercise-Induced Oxidative Stress in Healthy Volunteers; an Exploratory Study - Maha Noordin Abu Hajleh; Emad Abdol Sahib Al-Dujaili (Tabriz University of Medical Sciences, 2023)
Purpose: Evidence suggests that turmeric intake can improve antioxidant defense, blood pressure (BP), ageing and gut microbiota. The effects of turmeric concentrate (curcumin) intake on cardiovascular risk factors and exercise induced oxidative stress were investigated. Methods: A randomized placebo-controlled study was performed to assess the effects of turmeric extract in healthy volunteers before and after a 30 min exercise bout. Participants (n=22) were given either turmeric concentrate or placebo supplements. Anthropometry, BP, pulse wave velocity (PWV), biomarkers of oxidative stress, perceived exertion and lipid peroxidation were assessed. Results: In the turmeric group, the expected BP response to exercise following turmeric was blunted and the increase was not significant compared to basal values followed by a decrease in final BP and PWV values. There were no significant differences in all baseline parameters between the placebo and the curcumin groups (P>0.05). A significant increase was observed in urinary antioxidant power (P=0.031) and total polyphenol levels (P=0.022) post turmeric intervention. The distance ran by the participants taking turmeric was significantly longer (P=0.005) compared to basal value. Those who took the placebo did not show significant changes. Conclusion: Our study suggests that turmeric concentrate intake can reduce BP and improve antioxidant, anti-inflammatory status and arterial compliance. Turmeric may improve exercise performance and ameliorates oxidative stress. Larger studies are warranted to validate these findings and test more cardiovascular risk factors.